Democracy in an Age of Networked Control. - López, Leopoo (Journal of Democracy, 2026)
Contemporary repression, this essay contends, is no longer mainly the visible work of censors and jailers; it is networked, algorithmic, and invisible, teaching millions who have never been imprisoned to hesitate and self-censor. Freedom, the author insists, is not an abstraction but a set of concrete capacities—to communicate, move, organize, and connect—that these distributed systems of control quietly strip away before overt repression is ever needed. The response must therefore itself be networked: building resilient, distributed infrastructure that keeps those capacities genuinely accessible. This is not defeatism but a structural argument—leadership and courage still matter yet cannot succeed inside systems an adversary controls. Whoever controls the infrastructure of freedom, the author concludes, will shape the future of democracy.